IJCM_299A: Clinical profile of patients with dengue: a cross-sectional study from a tertiary care hospital, Karnataka - Nivetha S; Kumar Ashwini; Saravu Kavitha; Eshwari K (Wolters Kluwer Medknow Publications, 2024)
Background: Dengue fever (DF) are among the most important mosquito- borne diseases of the Indian subcontinent and have become a major global public health concern. Its clinical manifestations of which vary from influenza- like illness (DF) to life-threatening dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS). The purpose of the study was to find out the mode of presentation, biochemical profile and complications of Dengue cases in an apical level. Objectives: 1. To identify socio-demographic characteristics and clinical features; 2. To document the disease specific management and outcomes Methodology: A cross-sectional study of admitted patients was conducted in the department of medicine and Infectious Diseases over a period of 9 months (15/2/2023 -15/11/2023). Patients aged above 18 years with serology proven (nonstructural protein 1 [NS1]/dengue immunoglobulin M [IgM]) DF were included in this study. Their Socio demographic Details, clinical and laboratory data was recorded and analyzed. Results: Preliminary Results: Out of 125 cases, - 89 (71.2 %) patients were males and 36 (28.8%) were females. - The most common presentations were fever (96%) followed by Nausea/vomiting (40%), Headache (35%) and myalgia (31%). - Dengue NS1 and IgM antibodies were positive in 87.3% and 88.12% of the patients, respectively. - the incidence of DF, DHF, and DSS was 87.2, 11.2, and 1.6% respectively. - Shock, bleeding, and elevated serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase levels predicted adverse outcome. Conclusion: DF can present with a spectrum of clinical manifestations ranging from mild self-limiting illness to severe fatal disease. It can have varied and multi-systemic manifestations which can go unrecognized. Continuous seroepidemiological surveillance is essential to control outbreak and minimize morbidity and mortality.